Uma proposta didática para o ensino de geometria no ensino médio integrado em agropecuária com uso do Geogebra - Barbosa, Ivaldo Rodrigues (2024)
This dissertation addresses the need to improve the teaching of Geometry in the Mid Level Technical Course in Agriculture in an integrated format, exploring the integration of digital technologies, with an emphasis on the use of GeoGebra software as a tool in the teaching-learning process. The teaching of mathematics in integrated technical courses crosses different moments of the curricular proposal and, therefore, requires teaching processes that enable the contextualization and articulation between general training knowledge and technical-scientific training. The contextualization of the problem is based on the observation of recurring difficulties in teaching Geometry within a professional technical context, such as the Agriculture course. These difficulties are amplified by the lack of interactive methodologies that dialogue with the specific demands of this area, being essential to promote pedagogical approaches that articulate mathematical content with agricultural practice. The general objective is to analyze the contributions of the elements and functions of the Geogebra application in the teaching of Plane and Spatial Geometry in the integrated technical course in agriculture, with a view to developing the educational product related to the master's research. The research was carried out at the Manaus Zona Leste Campus (CMZL) of the Federal Institute of Education, Science and Technology of Amazonas (IFAM). Five teachers who work in the integrated technical course in agriculture participated in the research, as well as the collaboration of the first-year students of the Agriculture course. The methodological path used was the qualitative approach and field research in which the data were obtained through the application of a questionnaire and interview for data collection. The results obtained demonstrated that the teachers are unaware of the potential of the Geogebra software in teaching geometry as well as being an articulating tool in the curricular proposal of the course with a view to polytechnic training. The Educational Product developed aims to contribute to teaching practice during theoretical and practical classes in the Intermediate Level Technical Course in Agriculture in an Integrated Form, containing guidelines for using the GeoGebra software.